Differential scanning calorimetric characterization of pharmaceutical powder blend uniformity in a laboratory-scale V-blender - Mahmood, Syed; Hilmi, Nur Nadhirah; Husain, Nur Khairunnisa; Chatterjee, Bappaditya; Mandal, Uttam Kumar (Elsevier, 2015)
Testing of powder blend uniformity is one of the important steps during formulation development and routine commercial production of pharmaceutical products. Pharmaceutical industries heavily rely on chemical analysis by UV or HPLC for the same. However, the chemical methods are time consuming, need a few grams of powder sample, and they are not green in nature. The objective of this research is to explore the use of DSC as an alternative of UV analysis to assess the powder blend uniformity of a binary mixture of metformin hydrochloride and HPMC (5:95 w/w) at 50% and 60% occupancy of a laboratory-scale V-blender. Samples were withdrawn at 5, 10, 15, and 20 min intervals each of the top, middle, and bottom positions of the blender. Samples from all three locations at all time-points were found to have similar concentrations by both methods with the maximum RSD below 26%. Percent of metformin HCl recovery from the powder mixture after 20 min was comparable to the DSC method (2.68 ± 0.22% and 2.29 ± 0.14% at 50% and 60% occupancy, respectively) and UV method (2.66 ± 1.10% and 2.60 ± 0.32% at 50% and 60% occupancy levels, respectively). DSC, after a careful evaluation of drug and excipient specific interaction, can be considered as an alternative of pharmacopoeial spectrophotometric or chromatographic methods for powder blend uniformity assessment at various stages of pharmaceutical product development and its commercial production.